Enhancing Climate Change Resilience: Ethnicity and Gender-Sensitive in Climate-Smart Agriculture Options Implemented in Vietnam - Anh, Nguyen Hung; Vinh, Bui Le (AGRARIS: Journal of Agribusiness and Rural Development Research, 2025)
Agricultural livelihoods in Vietnam’s Northern Mountain Region are shaped by ethnic diversity, gendered labor dynamics, and growing exposure to climate change. This study seeks to examine social disparities, particularly those related to gender and ethnicity, in farmers’ adoption of Climate-Smart Agriculture Technologies and Practices (CSA T&Ps) to enhance climate change resilience in the Northern Mountain Region of Vietnam. Socioeconomic factors, the climate-related knowledge, perception, and attitude of local farmers influencing the adoption of CSA T&Ps were tested using dichotomous logistic regression. The results revealed significant ethnic disparities affecting access to climate-smart agriculture (CSA) training and resources in Vietnam’s Northern Mountain Region. While gender inequalities in CSA adoption were minimal, ethnic minority farmers encountered substantial barriers compared to majority groups, impacting their climate adaptation capacity. Key determinants of CSA adoption included participation in training, access to climate and agricultural extension services, and local perceptions of the impacts of climate change. These findings highlight the need for socially inclusive policies addressing ethnic and social disparities to enhance CSA scaling and build climate resilience in marginalized farming communities.